PENERAPAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW DI STMIK YADIKA BANGIL PADA MATA KULIAH LOGIKA MATEMATIKA - Majida Noviyanti (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2019)
This study was held to describe design and process of mathematical logic learning in STMIK Yadika Bangil by using jigsaw cooperative learning model of instruction, and to check its implementation effectiveness. The result of this study showed positive marks for all the aspects that had been evaluated, which are consist of students’ motivation, students’ attitude toward the jigsaw cooperative learning, students’ involvement in learning, and students’ achievement. The students’ achievement was evaluated by using the result of scoring toward students’ pre-test and post-test. The scoring rubric was used in scale from one to four. The pre-test result showed accumulation score of 49, or 40,83%. After the instruction where the jigsaw cooperative learning was used, students’ post-test accumulation score increased to 86 or 71,67%.